Aplasia Cutis Congenita: A Case Report - Tahani Magliah; Faiza Alghamdi (Karger Publishers, 2018)
Background: Aplasia cutis congenita is characterized by congenital focal absence of skin in a newborn. Case Report: A 45-day-old boy presented to the outpatient clinic of dermatology at King Abdul Aziz Medical City, Jeddah, Saudi Arabia, with a flat scalp lesion on the space of the anterior fontanel. There was a positive family history of such condition in his older brother's scalp, which resolved spontaneously within 3 weeks after labor, without any medical intervention. There were no associated hemangiomata or other congenital defects in his body. The case was admitted to the hospital. Ultrasound of the head showed bullae over the anterior fontanel, well-defined complex cyst, and an isolated subcutaneous lesion, with no evidence of intracranial extension. The baby was started on intravenous infusion of vancomycin (67 mg in dextrose 5% in water) for 3 days, but no improvement occurred to the scalp cyst. The baby started to receive 15 g of 2% mupirocin ointment, topically three times daily. After 2 days, the scalp cyst gradually decreased in size and became dry within 1 week. Follow-up after 3 months showed that the scalp lesion completely healed, leaving a very small atrophic scar and no further management of the lesion was needed. Conclusions: Aplasia cutis congenita is a rare condition of uncertain etiology, but consanguinity may play a role. Its management depends on its pattern, location, underlying causes, and associated anomalies.